Rutin inhibits DRP1-mediated mitochondrial fission and prevents ethanol-induced hepatotoxicity in HepG2 cells and zebrafish. Issue 1 (2nd January 2021) - Choi, Youngsook; Seo, Heymin; Cho, Mina; Kim, Joohee; Chung, Hak Suk; Lee, Icksoo; Kim, Min Jung
ABSTRACT: Excessive alcohol consumption causes the cellular and tissue damage. The toxic metabolites of ethanol are harmful to multiple organ systems, such as the central nervous system, skeletal muscles, and liver, and cause alcohol-induced diseases like cancer, as well as induce hepatotoxicity, and alcoholic myopathy. Alcohol exposure leads to a surge in hepatic alcohol metabolism and oxygen consumption, a decrease in hepatic ATP, and the rapid accumulation of lipid within hepatocytes. Several pathologies are closely linked to defective mitochondrial dynamics triggered by abnormal mitochondrial function and cellular homeostasis, raising the possibility that novel drugs targeting mitochondrial dynamics may have therapeutic potential in restoring cellular homeostasis in ethanol-induced hepatotoxicity. Rutin is a phytochemical polyphenol known to protect cells from cytotoxic chemicals. We investigated the effects of rutin on mitochondrial dynamics induced by ethanol. We found that rutin enhances mitochondrial dynamics by suppressing mitochondrial fission and restoring the balance of the mitochondrial dynamics. Mitochondrial elongation following rutin treatment of ethanol exposed cells was accompanied by reduced DRP1 expression. These data suggest that rutin plays an important role in remodeling of mitochondrial dynamics to alleviate hepatic steatosis and enhance mitochondrial function and cell viability.